Analisis Kepemimpinan Islami pada Era Modern - Maulidyah Amalina Rizqi; Abdul Kadir Alamudi (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – Leadership is a key factor in determining the directon and dynamcs of an organization. In the context of Indonesia, where the majority of the population is Muslim, the implementation of Islamic Leadership models has not yet been optimized, despite their strong foundation in moral, spiritual, and humanitarian values as exemplified by the Prophet Muhammad (PBUH) Objectives – This study aims to analyze the relevance and implementation of Islamic leadership values in the modern era, and to explore the ideal characteristics of an Islamic leader based on the Qur’an and Sunnah Design/ Methodology/ Approach – This research adopts a qualitative approach using literature review as the primary method. Data were analyzed from various relevant soruces discussing the theory and practice of Islamc leadership and its application in contemporary contexts. Findings – The study finds that the principles of Islamic leadership-such as honesty, exemplary conduct, justice, and service-remain relevant and can serve as a solution to leadership crises driven by political power in the modern era. Islamic leaders are expected to carry out their duties with sincerity, as a form of worship, and with a focus on communal benefit. Conclusion – Islamic leadership is not only compatible with the demands of modern tmes but also offers a framework for improving leadership quality across sectors. A deep understanding of Islamic values and prophetic character is essential in shaping effective and moral leadership Research Implications – This research provides a theoretical foundation for developing leadership models based on Islamic values in contemporary organizations and contributes to the literature on leadership from a religious perspective. Research Limitations – This study is limited to a conceptual approach through literature review and does not include empirical data from filed practices, indicating the need for further research through case studies or surveys.